Seismic vulnerability analysis of irregular and regular structures using fragility curve - Rehni Setiati; Masrilayanti; Ruddy Kurniawan; Asri Luthfi Ainy; Sourkan Sulleyman (E3S Web of Conferences)
The demand for innovative and visually appealing building designs according to specific desires or needs has led to many structures being built with irregularities. High-rise buildings with structural irregularities are at a higher risk of collapse during an earthquake if they are not designed and constructed properly according to existing regulations. Some buildings have non-uniform floor heights, which can lead to uneven distribution of stiffness throughout the structure vertically. Excessive height of one floor compared to the floor above it can potentially create an excessive soft story. Evaluating and assessing seismic vulnerability of structures is a major issue in earthquake-resistant design. This study discusses an analytical model for developing fragility curves by evaluating the seismic performance of a structure. The objective of this research is to determine and compare the estimated fragility levels of structures subjected to seismic loads between irregular structures with soft story irregularities and regular structures. Based on the results and discussion, it can be concluded that irregular structures (with soft story irregularities) have higher fragility levels compared to regular structures in both the x and y directions.